Effect of Encapsulated Artemisia aucheri. L Magnetic Nanogel Extract on Shoulder Block in Rat - Beiranvand, Siavash; Karimi, Arash (Drug Research, 2018)
Introduction Due to the severe pain generated after shoulder surgery, we aim to formulate and intravenously (IV) inject magnetic nanogel encapsulated Artemisia aucheri. L extract for inducing shoulder block in the rat.Methods Artemisia aucheri. L extract encapsulated magnetic nanoparticles (MNPs) was fabricated and tested in rat using paw withdrawal latencies (PWL) from thermal stimuli on the forepaw. The animals were divided into two groups; the untreated left forepaw (control group), and the test group with treated right forepaw. Sixteen (16) lab animals were used in this study, of which 3 in each of the two groups of the cumulative drug release experiments at 37°C and 43°C, and 5 in each of the two groups of PWL experiments.Results UV spectroscopy data shows that decreasing the pH of the fabricated nanocomposite has an influence on the extract release rate than increasing its temperature.Conclusions The present study gave a proof of inducing a shoulder block in rat by IV injection administration of NIPAAM-MAA/Arthemisia aucheri. L extract complexes and magnet application to the shoulder. This will be a prospective formulation if a lower pH and temperature is considered for optimum release of this nanoanesthetics, thus, this can be translated into clinical practice for future applications.
Keywords: Artemisia aucheri. L; shoulder block; nanogel; magnetic nanoparticles; anesthesia